Meneroka relevan budaya Islam dalam penjagaan kejururawatan merentas budaya dan agama: semakan skop = [Exploring the relevance of Islamic culture in cross-cultural and religious nursing care: a scoping review] - Mohamad Ismail, Mohamad Firdaus; Mokhtar, Ahmad Effat; Shahadan, Siti Zuhaidah (Penerbit Universiti Sains Islam Malaysia, 2024)
This scoping review explores transcultural and religious care in nursing, with a focus on Islamic perspectives in hospital settings. Studies published from 2018-2023 found in three leading databases will be reviewed, including JSTOR, PubMed and Scopus. Quality assessment was performed using the Joanna Briggs Institute (JBI) Evidence Synthesis framework, involving two authors in a literature review. Only five articles were systematically reviewed based on their completeness for quantitative synthesis on design, population, methodology and instrumentation. This scoping study aims to understand health care providers' concerns about Islamic obligations in health care and patients' concerns about Islamic obligations when receiving hospital treatment. This study identified a lack of research on the interaction between ethical, cultural and religious factors in the health care environment, with particular emphasis on the need for Muslim health care providers to address the cultural and religious needs of non-Muslim patients. In conclusion, the scope of the review underlines the need for future research to focus on the complex dynamics between Muslim nurses and non-Muslim patients to better understand and meet the cultural and religious needs of hospitalization.